The uncool : [large type] a memoir - Crowe, Cameron, 1957- (Thorndike Press large print biographies and memoirs., 2025)
"Cameron Crowe was an unlikely rock and roll insider. Born in 1957 to parents who strictly banned the genre from their house, he dove headfirst into the world of music. By the time he graduated high school at fifteen, Crowe was contributing to Rolling Stone. ... [this memoir] offers a front-row ticket to the 1970s, a golden era for music and art when rock was young. It's also a surprisingly intimate family drama. This memoir is an essential read for music lovers or anyone chasing their wildest dreams. At the end of that roller-coaster journey, you might just find what you were looking for: Your place in the world"--